1988
DOI: 10.5271/sjweh.1925
|View full text |Cite
|
Sign up to set email alerts
|

Risk of non-Hodgkin's lymphoma among men occupationally exposed to organic solvents.

Abstract: OLSSONH, BRANDTL. Risk of non-Hodgkin's lymphomaamong men occupationallyexposedto organic solvents. Scand J Work Environ Health 14(1988) 246-251. An occupational history of exposure to organicsolvents,definedas dailyoccupational exposure for at least one year, wasmore commonamong 167 men with newly diagnosed non-Hodgkin's lymphoma than among 130 healthyreferents from the general population (38 versus 14 070). Categorization in five-year age groups gave 3.3 as a Mantel-Haenszel estimate of the odds ratio (95 07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 20 publications
2
23
1
3
Order By: Relevance
“…The risk increase ratios vary between 0.9 and 4.7 (Hardell et al, 1981;Pearce et al, 1986, Woods et al, 1987Olsson et al, 1988;Kogevinas et al, 1995;Pahwa et al, 2012). The relationship between the use of pesticides and development of NHL has also been investigated in two cohort studies, which identified a borderline increase in risk (Kogevinas et al, 1997;Bertazzi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The risk increase ratios vary between 0.9 and 4.7 (Hardell et al, 1981;Pearce et al, 1986, Woods et al, 1987Olsson et al, 1988;Kogevinas et al, 1995;Pahwa et al, 2012). The relationship between the use of pesticides and development of NHL has also been investigated in two cohort studies, which identified a borderline increase in risk (Kogevinas et al, 1997;Bertazzi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, case-referent studies have suggested that occupational exposure to solvents might be a risk factor for non-Hodgkin's lymphoma (25,26). Exposure to ionizing radiation, especially radium, is the only well-established occupational agent related to bone cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although this remains mostly unexplained, it has been suggested that greater exposure to environmental carcinogens, particularly to pesticides and solvents, may be responsible. [4][5][6][7] Moreover, susceptibility to genomic damage has also been linked to dietary folate deficiency, because this metabolic pathway is important for both nucleotide synthesis and methylation. The genes encoding folate metabolic enzymes display several single nucleotide polymorphisms (SNPs)-for example, methylenetetrahydrofolate reductase (MTHFR C677T and MTHFR A1298C), serine hydroxymethyltransferase (SHMT C1420T), and methionine synthase (MS or MTR A2756G)-and variable number tandem repeats (VNTRs) for thymidylate synthase (TS or TYMS VNTR 2R and 3R).…”
Section: Introductionmentioning
confidence: 99%